Balance deficit among diabetic polyneuropathy Saudi patients - Abd El-Kader, Shehab Mahmoud; Refaey, Neveen; Atiaa, Amany Gomaa; AlKhateeb, Afnan M.; AlFawaz, Saad S.; Neamatallah, Ziyad A.; Umar M. Alabasi; Gaowgzeh, Riziq Allah Mustafa; Atiaa, Amany Gomaa; Salwa R. El-Gendy; Mohamed F. El- Banna; Tamer M. El-Saeed; et al. (J Med Rehab Sci, 2025)
Background: Currently, the risk of fall is high among diabetic patients in Saudi Arabia. Nowadays, the interest is direct towards prevention of fall through the prospective research studies trying to reduce the fall risk. Objective: The present study was intended to detect the fall incidence among diabetic Saudi patients with polyneuropathy. Material and Methods: Two hundred Saudi patients with type 2 diabetes mellitus, their age ranged 35-55 years, were divided into 2 groups: subjects with diabetes and with established peripheral neuropathy (diabetic peripheral neuropathy [DPN] group) to whom diabetes was diagnosed by clinical guidelines and balance performance was assessed using the Functional Reach Test (FRT), the Timed Up and Go Test (TUG) and Berg Balance Scale (BBS). Results: There were significant differences between groups have been detected for BBS and FRT which was significantly lower for diabetic patients with peripheral neuropathy compared with diabetic patients. While, significant higher values for diabetic patients with peripheral neuropathy were also detected for TUG compared with diabetic patients. Conclusion: We provide evidence that diabetic patients with peripheral neuropathy have greater balance deficit than diabetic patients without peripheral neuropathy. Key Words: Balance; Type 2 Diabetes Mellitus; Diabetic Peripheral Neuropathy.